Demography Characteristic of Married Women and Abortion Behavior in Unwanted Pregnancy - Suherni, Suherni; Raharjo, Bambang Budi (Universitas Negeri Semarang, 2018)
Unwanted pregnancy is a reproductive health problem that has an impact on high maternal mortality and unsafe abortion rates, Indonesia is one of the developing countries with maternal mortality rates (MMR) in 2015 researching 305 per 100,000 live births, this number is still far from the target of sustainable development goals (SDGs) to reduce MMR to 70 per 100,000 live births in 2030 (Ministry of Health, 2017). The purpose of this study was to determine the effect of married women demographic characteristics and unsafe abortion behavior on unwanted pregnancies in the Indonesian Family Planning Associating (PKBI) in Pemalang district. This research is a mixed method research with a quantitative explanatory design. The samples of the study were married women with unwanted pregnancies totaling 287 respomdents, with purposive sampling. Data analysis used chi square and logistic regression. Meanwhile, to support quantitative data from unsafe abortion behavior, eight informants were taken as qualitative data sources through interviews. The results showed that the characteristics of age, income and number of children were significantly associated with unsafe abortion behavior while the demographic caharacteristics that most affected the behavior of unsafe abortion were high risk age (p. 006 with OR 2,917) and the number of children was more than 2 (p. 0,044 with OR 2.069). Unwanted pregnancies in married women generally occur in old age whose already have enough children. Plan a pregnancy and arrange with contraceptive methods, so that the number of mobility and mortality associated with unsafe abortion can be reduced.